Ana on the edge - Sass, A. J. (Little, Brown and Company, 2020)
Ana-Marie Jin, the twelve-year-old U.S. Juvenile figure skating champion, has two different identities to juggle while on the ice after she meets transgender boy Hayden, who mistakes Ana for a boy. Ana does not correct Hayden, deciding to pretend to be a boy in order to not have to wear a princess-themed outfit for the next season's program. Ana and Hayden's friendship develops over a season filled with confusion and questions about gender identity and what it means to think she is gender nonbinary.